Far beyond Lua Branca: the chamber songs of Francisca Gonzaga - Mestrinho Sylvestre, Maria Luiza (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
This article discusses Chiquinha Gonzaga's songs for voice and piano from the point of view of the Brazilian Art Song. Although the composer's work has always been considered more Brazilian popular than classical music, several of her songs have chamber music characteristics; therefore, it is suitable for interpretation by classical singers. Also, the source of her songs is sheet music, as she mainly worked before radio and recording. The biased view that considers her music exclusively popular has been questioned, and arguments are presented using the historical context in which the composer lived. Likewise, the article tried to find examples of songs with characteristics of art song, and therefore, suitable for lyrical interpretation. It presents some examples justifying their use in the repertoire of singers and lyrical singing students. This article aims to contribute to the awareness that studying and singing more of Chiquinha Gonzaga's songs is needed.